KONSEP PENDIDIKAN KARAKTER DITINJAU DARI PERSPEKTIF PSIKOLOGI ISLAM - Rahimi Rahimi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The journal examines about the character education concept in terms of the Islamic Psychology Perspectives. What the intention of knowing on the character education concept in terms of Islamic psychology. This study was carried out using the library research methode (Library Research). The result of this research indicate that character education is oriented towards behavior, commandable morals and manners that contain agreed manners in the interpersonal environment. And than character education can be done by fostering social, morals and religious value merged, so that attitude, mentality, morals, and personality according to teaching of the Islamic religion.